Pengaruh brand image dan penggunaan layanan paylater terhadap perilaku konsumtif mahasiswa program studi Pendidikan Ekonomi Universitas PGRI Ronggolawe Tuban - Yuma Putri Safara (Jurnal Pendidikan Ekonomi (JUPE), 2026)
This study aims to analyze the effect of brand image and the use of PayLater services on the consumptive behavior of students in the Economic Education Study Program at Universitas PGRI Ronggolawe Tuban. This study employs a quantitative approach using a survey method. Data were collected through questionnaires distributed via Google Forms to respondents. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that there is no significant relationship between students’ perceptions of brand image and their consumptive behavior. In contrast, the use of PayLater services has a positive and significant effect on students’ purchasing behavior. Furthermore, the use of PayLater also influences purchasing habits and students’ perceptions of brands. Overall, both variables contribute to explaining variations in students’ purchasing behavior. The findings also show that in making purchasing decisions, students tend to prioritize the ease of using PayLater services over their perceptions of brand image. Therefore, improving financial literacy is essential to help students manage their finances wisely and use PayLater services more responsibly.